Understanding ozone‐meteorology correlations: A role for dry deposition. Issue 6 (31st March 2017) - Kavassalis, Sarah C.; Murphy, Jennifer G.
Abstract: Observations of coincident high relative humidity and low surface ozone are common in air quality data sets, but models underpredict the strength of this correlation. We perform a statistical analysis of 28 years of ozone and meteorology observations taken as part of the Clean Air Status and Trends Network across the United States and find that vapor pressure deficit (VPD) is the strongest predictor of midday ozone in the spring, summer, and fall, and this correlation is strongest at sites with the largest leaf area index. We argue that stomatal regulation of dry deposition, which is known to have a VPD dependence that is not typically included in model parameterizations, can explain this relationship. Using a box model of ozone production and loss, we show that a negative ozone‐humidity slope is only achieved by the inclusion of VPD‐dependent dry deposition, suggesting that this mechanism may explain the observed ozone‐humidity correlation. Key Points: Vapor pressure deficit is the strongest predictor of surface ozone over much of the USA from the spring to fall The ozone‐VPD correlation, and ozone‐humidity correlation, is explained by VPD‐dependent dry deposition Stomatally controlled dry deposition may play a significant role in controlling day‐to‐day variability in ozone during the growing season Plain Language Summary: Across the United States in the summer, days with severe ozone pollution frequently occur on days with low relative humidity. Why the strong relationship between ozone pollution and relative humidity exists has been a bit of a mystery, as air quality models underpredict the strength of this relationship. We show that correlation between ozone and humidity can be explained by dry deposition—that is, the uptake of ozone by trees. When relative humidity is high, trees open their stomata (pores for exchanging CO2 and water vapor) and then unintentionally take up ozone. When relative humidity is low, trees close their stomata so they do not dry out, and thus do not remove ozone from the air, allowing it to build up. We show that during the growing season, vapor pressure deficit (a good surrogate for whether stomata are open or closed) is the best predictor on average of ozone levels, suggesting that trees play an important role in regulating day‐to‐day ozone pollution.